2016
DOI: 10.1021/acscatal.6b00646
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Transient Kinetic Studies of the Acetoxylation of Toluene over Pd–Sb/TiO2

Abstract: A combination of steady-state catalytic tests, transient studies with isotopic tracers, and kinetic modeling was used to derive detailed insights into the individual reaction pathways in the course of toluene acetoxylation over a Pd−Sb/ TiO 2 catalyst. This reaction can be considered as an environmentally friendly route for the production of benzyl alcohol. Benzyl acetate and benzaldehyde are the only products formed from toluene, while acetic acid gives CO 2 in addition to benzyl acetate. The Arrhenius plots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Similar isotopic decay trends to non-zero steady states involving 16 [23]. Similar non-zero decays have also been observed for the case of oxygen-exchange during CO oxidation over Au/TiO 2 [38] and other catalytic reactions [25]. The responses for N 16 O 18 O and N 18 O 2 increased slightly to new steady states.…”
Section: Oxygen Path Tracing During No Oxidation With 18 O 2 Switchsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar isotopic decay trends to non-zero steady states involving 16 [23]. Similar non-zero decays have also been observed for the case of oxygen-exchange during CO oxidation over Au/TiO 2 [38] and other catalytic reactions [25]. The responses for N 16 O 18 O and N 18 O 2 increased slightly to new steady states.…”
Section: Oxygen Path Tracing During No Oxidation With 18 O 2 Switchsupporting
confidence: 76%
“…These promoters enhance the retention of nitrogen forming precursors leading to a larger delay in the N 2 transient in comparison to the unpromoted catalyst [24]. In another interesting example, the mechanism of toluene acetoxylation catalyzed by supported Palladium has been studied by SSITKA [25]. Transient kinetic analysis demonstrated that despite both lattice oxygen and adsorbed oxygen contributing to the activation of the reactant acetic acid, it was the latter that promotes the oxidation of acetic acid to undesired CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The SSITKA setup used in this work has been described in detail in our previous publication. 70 The catalyst (50 mg) was loaded into a fixed-bed quartz reactor and initially reduced at 400 °C under H 2 :N 2 = 1:1 (12 mL min −1 ) for 2 h. Hereafter, the reactor was cooled down to 300 °C in Ar. Finally, a CO 2 :H 2 :Ar = 1:11:7 feed was introduced into the reactor to achieve a gas-hourly space velocity (GHSV) of 36,000 mL g cat −1 h −1 .…”
Section: Steady-state Isotopic Transient Kinetic Analysis (Ssitka)mentioning
confidence: 99%
“…The SSITKA setup used in this work has been described in detail in our previous publication . The catalyst (50 mg) was loaded into a fixed-bed quartz reactor and initially reduced at 400 °C under H 2 :N 2 = 1:1 (12 mL min –1 ) for 2 h. Hereafter, the reactor was cooled down to 300 °C in Ar.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…For example, carbon oxide, as the most common side product, always appears in various proportions due to unavoidable total oxidation, which is the focus of selectivity control. Usually, the activation energy of oxidative dehydrogenation is lower than that of overoxidation to CO 2 on effective ammoxidation catalysts. , Based on the Arrhenius equation, it can be deduced that the ratio of the intrinsic reaction rates between the two subreactions decreases with the rise of reaction temperature. Therefore, one of the key methods to improve the selectivity is to conduct the reaction at a lower temperature.…”
Section: Introductionmentioning
confidence: 99%